2x+3x-8+9=5x-x+12-8

Simple and best practice solution for 2x+3x-8+9=5x-x+12-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+3x-8+9=5x-x+12-8 equation:


Simplifying
2x + 3x + -8 + 9 = 5x + -1x + 12 + -8

Reorder the terms:
-8 + 9 + 2x + 3x = 5x + -1x + 12 + -8

Combine like terms: -8 + 9 = 1
1 + 2x + 3x = 5x + -1x + 12 + -8

Combine like terms: 2x + 3x = 5x
1 + 5x = 5x + -1x + 12 + -8

Reorder the terms:
1 + 5x = 12 + -8 + 5x + -1x

Combine like terms: 12 + -8 = 4
1 + 5x = 4 + 5x + -1x

Combine like terms: 5x + -1x = 4x
1 + 5x = 4 + 4x

Solving
1 + 5x = 4 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
1 + 5x + -4x = 4 + 4x + -4x

Combine like terms: 5x + -4x = 1x
1 + 1x = 4 + 4x + -4x

Combine like terms: 4x + -4x = 0
1 + 1x = 4 + 0
1 + 1x = 4

Add '-1' to each side of the equation.
1 + -1 + 1x = 4 + -1

Combine like terms: 1 + -1 = 0
0 + 1x = 4 + -1
1x = 4 + -1

Combine like terms: 4 + -1 = 3
1x = 3

Divide each side by '1'.
x = 3

Simplifying
x = 3

See similar equations:

| -z^2= | | -5+13=16x-3-15x | | (9+u)(5u+2)=0 | | -3v+7v-v= | | x-0.2x=0.8 | | x+5.2=6.8+2(x-0.2) | | (z+8)(z+1)=0 | | x-(-7-3x)=-5 | | (z+8)(2+1)=0 | | x-0.2x=135.72 | | x-7-3x=-5 | | 0.2b-3=0.7+1.5 | | -2x+3=9 | | -6n+9=-5n-19 | | 8(3x-5)=4(6x+3) | | 8x+6-9x=2 | | 3x+2x+5=4x-2 | | (1-w)(3w-5)=0 | | -2x-3=-9 | | 3w-5=0 | | 14x-2=0 | | 3y=-5x+12 | | 9z=-45 | | 8x-4x+2=48 | | x^3-x^2-16=20 | | 8(3x-5)=(6x+3) | | 2Inx=4 | | y=5-5x | | 2x+5=156 | | 10+m=19-2m | | m^3+27n^3=0 | | X^2+8=-9 |

Equations solver categories